A brief mindfulness intervention improves electrophysiological markers of attention in meditation-naïve individuals: the moderating role of inattention symptoms - Yu, Xiaoqian; Vinci, Christine; Potts, Geoffrey F. (Frontiers in Psychology, 2025)
BackgroundAttention regulation is crucial for mindfulness practice; however, the influence of baseline attention ability on mindfulness training outcomes remains underexplored. This study examined the effects of a brief mindfulness intervention on attention and investigated whether baseline inattention symptoms moderated these effects in meditation-naïve university students.MethodsThis study employed a pretest-posttest, between-groups experimental design. Meditation-naïve university students (n = 121, aged 18–31, 69% women) were randomly assigned to either a mindfulness group, which engaged in 10 min of guided mindful breathing, or a control group, which listened to a talk on green living. Baseline attention was assessed using the Adult ADHD Self-Report Scale (ASRS), and attentional changes were measured via EEG recorded during a visual novelty oddball task.ResultsBoth groups showed increased post-intervention P3b amplitudes, an electrophysiological indicator of attention. However, the mindfulness group exhibited a significantly greater increase compared to the control group. Importantly, inattention symptoms moderated this effect: participants with higher inattention symptoms in the mindfulness group showed a greater increase in P3b amplitude, while those in the control group showed a decrease.ConclusionThese findings highlight the importance of considering individual attentional profiles when designing mindfulness-based interventions. Tailoring mindfulness training based on baseline attention levels may enhance its cognitive benefits. Future research should explore additional potential moderators of mindfulness training outcomes and clinical conditions (e.g., anxiety or depression) that may influence attentional functioning and responsiveness to mindfulness practice.